Eksplorasi Strategi Pemasaran: Kajian Kasus Observasi Online dengan menggunakan Matrix S.W.O.T. - Antonius Felix, Dimas Okta Briyanti, Jessica Amelia, Modesta Bancin, Chyntia Angelyna, Melvina Felic (Jurnal Mirai Management, 2023)
Namaaz Dining, located in South Jakarta, has successfully captivated culinary enthusiasts with its exclusive food concept and unique culinary experience based on Molecular Gastronomy. Despite achieving success in attracting customers, the restaurant faces significant challenges related to limited space and long queues, which can impact the customer experience with extended waiting times. This study aims to conduct a marketing strategy analysis using the SWOT method for Namaaz Dining. Through observation based on customer reviews and comments on the Trip Advisor platform, this research identifies factors influencing consumer interest in Namaaz Dining and explores strategic opportunities that can be optimized. The research results are expected to assist Namaaz Dining in developing a stronger marketing strategy, focusing on customer satisfaction, and expanding its market reach. The contribution of this research is intended to benefit not only Namaaz Dining but also to provide theoretical and practical insights into restaurant marketing strategies and customer management. Keywords: Unique Culinary, Gastronomy, Marketing Strategy, Qualitative, Marketing Communication